Pengaruh Gini Ratio Dan Apbd Per Kapita Terhadap Indeks Pembangunan Manusia Di Provinsi Nusa Tenggara Timur - Albajili, Hanif Aqil; Samsuddin, M. Afdal (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to examine the influence of income inequality and regional budget expenditure per capita on the Human Development Index (HDI) in East Nusa Tenggara Province. HDI serves as a key metric in assessing the success of human development, encompassing dimensions such as education, health, and standard of living. Income inequality is represented by the Gini Ratio, while regional expenditure per capita reflects the fiscal capability of local governments to deliver public services. The analysis employs annual secondary data from 2014 to 2024 using a multiple linear regression method. The findings of this study are expected to offer empirical insights for formulating equitable and sustainable human development policies in regions facing fiscal and structural limitations such as East Nusa Tenggara.